Video abstract production guide - Ferreira, Miguel; Lopes, Betina; Granado, António; Siopa, Catarina; Gaspar, Hugo; Castro, Helena; Castro, Sílvia; Loureiro, João (Frontiers in Communication, 2023)
Video abstracts are audio-visual representations of a scientific abstract that a researcher can use to complement an article. As a science communication tool, they stand as a novel and exciting way to present scientific discoveries, explore new formats, and reach new audiences. In this practice insight, we share the experience of creating a video abstract in Ecology, explaining and exemplifying the different stages of the process: selecting the paper, writing the script, producing the video, editing the video and promoting the film. Sharing the setbacks and wins of a video collaboration between researchers and science communicators, we hope to be a valuable contribution to all the people starting and already working in the field.